PENGARUH PEMBERIAN PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN LANSIA TENTANG PENCEGAHAHAN KEKAMBUHAN GOUT ARTHRITISH DI PANTI TRESNA WERDHA INA- KAKA AMBON - Petriana Mahmud; Rizky Amalia Hunusalela (Pasapua Health Journal, 2021)
Introduction: Ghout arthritis is a disease characterized by sudden attacks, recurring and accompanied by pain due to deposits of monosodium urate crystals. In Maluku the prevalence of joint disease based on a diagnosis is 5.08% with a total of 3,329 people in Ambon city (Riskesdas Maluku, 2018). In 2020, there were 30 cases of Gout Arthritis sufferers from the January-June period, out of 46 elderly people living in the Ina Kaka Ambon Nursing Home. The purpose of this study was to determine the knowledge of the elderly about preventing recurrence of gout arthritis before and after providing health education at the Tresna Werdha Ina Kaka Ambon Institution. Methods: This study used a pre-experimental design with a one-group-pre-test-posttest design approach to measure the difference in knowledge of the elderly before and after being given health education. The population in this study were 30 people using total sampling technique. Results: The results of the study showed that 27 respondents had prior knowledge of health education, 12 respondents (44.4%) had good knowledge, and 15 respondents (55.6%) had less knowledge. While respondents who had knowledge after being given health education who had good knowledge were 21 respondents (77.8%), and those who had less knowledge were 6 people (22.2%). Conclusion: BThat H0 was rejected and Ha was accepted because there was an effect of providing health education on the knowledge of the elderly about preventing recurrence of gout arthritis at the Tresna Werdha Ina-Kaka Institution Ambon . This shows that health education is able to increase the knowledge of the elderly about prevention of gout recurrence. It is recommended for the Tresna Werdha and Elderly Homes to be able to improve health education and knowledge about gout arthritis.